Metabolic abnormality and the proinflammatory state following hip joint surgery. (June 2011) - Dessouki, Omar; Mahomed, Nizar N; Gandhi, Rajiv
Hip surgery is one of the most commonly performed operations in adult orthopedics. A significant proportion of patients undergoing hip surgery are at considerable risk for postoperative complications secondary to age-related medical issues and the morbidity and mortality associated with hip fractures. Inflammation has been shown to play a pivotal role in the host response to total hip arthroplasty and hip fracture surgery. A newly evolved area of research aimed at investigating the complex biochemical roles of the immune system, cytokine cascades and adipose tissue in the systemic inflammatory response to hip surgery has already identified a few central players in this response, namely IL-6, leptin and cortisol. This new area of study has also begun to define the influence of the metabolic syndrome on creating an underlying, chronic state of low-grade systemic inflammation that may predispose patients to postoperative complications in the setting of hip surgery. The ultimate goal of researchers is to develop therapeutic strategies targeted at modulating and controlling postoperative inflammation. In doing so, it is believed that we can improve the biochemical environment in which hip surgery is performed, ameliorate patient outcomes in the realm of pain and function, and predict and reduce postoperative complications associated with aberrant immune and inflammatory responses.